Does Kinesiophobia Associated with Poststroke Neuropathic Pain and Stroke Severity? - Koca, Tuba Tülay; Gülkesen, Arif; Nacitarhan, Vedat; Koca, Özlem (My University, 2019)
Objective: Kinesiophobia is defined as fear of acting due to belief of predisposition toinjury. It causes physical activity limitation. There are many factors in the older age populationthat affect poor recovery after stroke. Central pain after stroke is a neuropathic pain disorder withunknown pathogenesis. Here, we aimed to evaluate association of kinesiophobia with poststrokecentral pain and the stroke severity in stroke patients at rehabilitation program. Material and Methods:Seventy-five (n=75) stroke patients with the mean age range of 55.5±13.1 year were includedin the study. The control group (n=78) consisted of healthy volunteers of similar age and gender.Age, gender, stroke duration, involved side, stroke type (ischemic, hemorrhagic, subarachnoid etc.)were recorded in all patients. The severity of stroke was assessed by the National Institute of HealthStroke Scale. Poststroke pain was assessed by the Self-Leeds Assessment of Neuropathic Symptomsand Sign pain scale. Kinesiophobia was assessed by the Tampa Scale for Kinesiophobia. Results: Ofthe patients, 53.3% were in acute, 20% were in subacute and 20% were in chronic period. Themean duration of the stroke was 13.6±22.2 years. The rate of right side involvement was 48% and58% was ischemic type. The mean Tampa score was 44±7.7 and was statistically higher than controlgroup. The mean National Institute of Health Stroke Scale score was 4.5±3.9; Self-Leeds Assessmentof Neuropathic Symptoms and Sign pain score was 7.2±6.7; the prevelance of neuropathicpain was 21.3% (n=16) and was similar with control group. Conclusion: Kinesiophobia was foundto be higher in stroke patients and was positively correlated with advanced age, disease duration andstroke severity. We should consider kinesiophobia in stroke rehabilitation programs.Keywords: Stroke; neurorehabilitation; aging; chronic pain; neuropathic pain; kinesiophobiaÖZET Amaç: Kinezyofobi, yaralanmaya yatkınlık inanışı nedeniyle hareket etmekten korkmak olaraktanımlanmaktadır. Fiziksel aktivite sınırlamasına neden olur. Yaşlı nüfusta inme sonrası kötüiyileşmeyi etkileyen birçok faktör vardır. İnme sonrası santral ağrı, patogenezi bilinmeyen bir nöropatikağrı bozukluğudur. Burada, rehabilitasyon programındaki inme hastalarında kinezyofobininpoststroke santral ağrı ve inme şiddeti ile ilişkisini değerlendirmeyi amaçladık. Gereç veYöntemler: Çalışmaya yaş ortalaması 55,5±13,1 yıl olan yetmiş beş (n=75) inme hastası dâhil edildi.Kontrol grubu (n=78) benzer yaş ve cinsiyette sağlıklı gönüllülerden oluşturuldu. Tüm hastalardayaş, cinsiyet, inme süresi, tutulan taraf, inme tipi (iskemik, hemorajik, subaraknoid vb.) kaydedildi.İnme şiddeti, Ulusal Sağlık Enstitüsü İnme Skalası ile değerlendirildi. İnme sonrası ağrı, Self-LeedsNöropatik Semptom ve Bulgu ağrı skalası ile değerlendirildi. Kinezyofobi, Tampa Kinezyofobi Skalasıile değerlendirildi. Bulgular: Hastaların %53,3’ü akut, %20'si subakut ve %20'si kronik dönemdeidi. İnme süresi ortalama 13,6±22,2 yıldı. Sağ tarafın tutulma oranı %48 idi ve %58’i iskemik tipti.Ortalama Tampa skoru 44±7,7 idi ve kontrol grubundan istatistiksel olarak daha yüksekti. OrtalamaUlusal Sağlık Enstitüsü İnme Skalası skoru 4,5±3,9 idi; Self-Leeds Nöropatik Semptom ve Bulguağrı skalası skoru 7,2±6,7 idi; nöropatik ağrı prevalansı kontrol grubu ile benzerdi ve %21,3 (n=16)idi. Sonuç: Kinezyofobi inme hastalarında daha yüksek bulundu ve ileri yaş, hastalık süresi ve inmeşiddeti ile pozitif korele idi. İnme rehabilitasyon programlarında kinezyofobiyi dikkate almalıyız.
Keywords: Genel ve Dahili Tıp; Rehabilitasyon; Nörolojik Bilimler